The Two-Systems Account of Theory of Mind: Testing the Links to Social- Perceptual and Cognitive Abilities - Meinhardt-Injac, Bozana; Daum, Moritz M.; Meinhardt, Günter; Persike, Malte (Frontiers in Human Neuroscience, 2018)
According to the two-systems account of Theory of Mind (ToM), understanding mental states of others involves both fast social-perceptual processes, as well as slower, reflexive cognitive operations (Apperly and Butterfill, 2009; Frith and Frith, 2008). To test the respective roles of specific abilities in either of these processes we administered 15 experimental procedures to a large sample of 343 participants, testing ability in face recognition and holistic perception, language, and reasoning. ToM was measured by a set of tasks requiring ability to track and to infer complex emotional and mental states of others from faces, eyes, spoken language and prosody. We used structural equation modeling to test the relative strengths of a social-perceptual (face processing related) and reflexive-cognitive (language and reasoning related) path in predicting ToM ability. The two paths accounted for 58% of ToM variance, thus validating a general two-systems framework. Testing specific predictor paths revealed language and face recognition as strong and significant predictors of ToM. For reasoning, there were neither direct nor mediated effects, albeit reasoning was strongly associated with language (r = 0.73). Holistic face perception also failed to show a direct link with ToM ability, while there was a mediated effect via face recognition. These results highlight the respective roles of face recognition and language for the social brain (Kennedy and Adolphs, 2012), and contribute closer empirical specification of the general two-systems account.